1990
DOI: 10.1118/1.596456
|View full text |Cite
|
Sign up to set email alerts
|

Levels of leakage radiation from electron collimators of a linear accelerator

Abstract: The leakage radiation from electron applicators used with our linear accelerator has been measured. For the applicators 6 X 6 to 25 X 25 cm size, the leakage was measured in the plane of the patient and on the sides of the applicators with the available electron energies of 6, 9, 12, 15 and 18 MeV. The levels were significant. The highest leakage on the side was for the combination of 6 X 6-cm applicator and 9-MeV electrons (32%) and in the plane of the patient for 25 X 25-cm applicator with 18 MeV (10%) relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Dose leakage from electron therapy has been the subject of limited investigation 1 , 2 , 3 , 4 , 5 , 6 A better understanding of the magnitude of out‐of‐field dose associated with this treatment modality is needed, particularly for newer models of linear accelerator. The importance of studying this issue was made clear by Yeboah et al, (7) who showed very high out‐of‐field doses when utilizing electron therapy, often largely exceeding out‐of‐field doses from comparable photon treatment fields.…”
Section: Introductionmentioning
confidence: 99%
“…Dose leakage from electron therapy has been the subject of limited investigation 1 , 2 , 3 , 4 , 5 , 6 A better understanding of the magnitude of out‐of‐field dose associated with this treatment modality is needed, particularly for newer models of linear accelerator. The importance of studying this issue was made clear by Yeboah et al, (7) who showed very high out‐of‐field doses when utilizing electron therapy, often largely exceeding out‐of‐field doses from comparable photon treatment fields.…”
Section: Introductionmentioning
confidence: 99%
“…The applicators are designed to allow scattered electrons and transmission radiations to escape outside the treatment beam as little as possible. However, it is well known that a non‐ignorable fraction of scattered and transmission radiations can escape from the applicator and induce unintended doses outside the treatment field 6 , 7 , 8 , 9 , 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that a non-ignorable fraction of scattered and transmission radiations can escape from the applicator and induce unintended doses outside the treatment field. (6)(7)(8)(9)(10)(11)(12) The two main components of out-of-field doses outside the applicator are bremsstrahlung photon contamination and scattered electrons. (11,13) The bremsstrahlung photons can be produced in different structures of the accelerator head and in the patient irradiated volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the leakage radiation on the outside surface of an applicator sidewall or just outside the applicator body can be prohibitively high. ( 1 5 ) This, in turn, leads to unacceptably high peripheral doses in the patient plane ( 1 3 ) and can be detrimental to the patient, especially when sensitive structures and/or the patient's skin is in close proximity to the applicator sidewall – as in the treatment of breast cancer involving the internal mammary lymph node chain (IMC) using a combination of parallel‐opposed photon tangents and an oblique “electron patch”. ( 6 , 7 ) Other clinical situations where the applicator leakage poses a significant risk to patients include exposure of the shoulders to leakage radiation when treating neck nodes at extended SSD, and exposure of the legs to leakage during testicular boosts for TBI.…”
Section: Introductionmentioning
confidence: 99%